Management and adherence to VTE treatment guidelines in a national prospective cohort study in the Canadian outpatient setting - Kahn, Susan R.; Springmann, Vicky; Schulman, Sam; Martineau, Josée; Stewart, John A.; Komari, Nelly; McLeod, Anne; Strulovitch, Carla; Blostein, Mark; Faucher, Jacques-Philippe; Gamble, Greg; Gordon, Wendy; Kagoma, Peter K.; Miron, Marie-José; Laverdière, David; Game, Melaku; Mills, Allan (Thrombosis and Haemostasis, 2012)
Documenting patterns and outcomes of venous thromboembolism (VTE) management and degree of adherence by clinicians to treatment guidelines could help identify remediable gaps in patient care. Prospective, clinical practice-based data from Canadian outpatient settings on management of VTE, degree of adherence with treatment guidelines and frequency of recurrent VTE and bleeding during follow-up was obtained in a multicentre, prospective observational study. From 12 Canadian centres, we assessed 868 outpatients with acute symptomatic VTE who received the low-molecular-weight heparin (LMWH) enoxaparin alone or with vitamin K antagonists (VKA), at baseline and at six months (or at the end of treatment, whichever came first). Index VTE was limb deep venous thrombosis (DVT) in 583 (67.2%) patients, pulmonary embolism (PE) with or without DVT in 262 (30.2%) patients, and unusual site DVT in 23 (2.6%) patients. VTE was unprovoked in 399 (46.0%) patients, associated with cancer in 74 (8.5%) patients, transient risk factors in 327 (37.7%) patients and hormonal factors in 68 (7.8%) patients. With regard to guideline adherence, 58 (7.3%) patients received <5 days LMWH and 114 (14.5%) had overlap <1 day. Among patients with cancer-related VTE, 59.5% were prescribed LMWH monotherapy and 43.2% received such treatment for >3 months. Only 38.1% of patients with transient VTE risk factors had received thromboprophylaxis. Our study provides useful information on clinical presentation, management and related outcomes in Canadian outpatients with VTE. Our results suggest there may be important gaps in use of thromboprophylaxis to prevent VTE and use of LMWH mono-therapy to treat cancer-related VTE.Note: Part of this study was presented as an Oral Abstract Presentation at the American Society of Hematology meeting, Dec. 4–7, 2010, Orlando, FL, USA.
Keywords: Venous thromboembolism; clinical practice guidelines; anticoagulation; cancer-associated thrombosis; prospective study